Factors influencing the effectiveness of The New Straits Times Press (M) Bhd Kuantan branch's distribution system / Anis Nadia Ismail - Ismail, Anis Nadia (Faculty of Business and Management, 2007)
This research is about a study on factors influencing the effectiveness of distribution system performed by The New Straits Times Kuantan branch. The New Straits Times Press (M) Berhad or affectionately known as NSTP is a well established firm and also one of the largest company in Malaysia, especially in the newspaper industry. Since the nature of the business is more on delivering products to consumers, therefore an effective distribution system is very essential to the firm.. In order to maintain its performance and to compete with its main rival, which is Utusan, NSTP should oversee all areas of its business performance. In most situations, distribution system plays a vital role in the firm's overall performance. By focusing in NSTP Kuantan branch, there are some problems and conflicts occurred during the newspaper distribution process. These may spoil the effectiveness of the system, and thus will affect the whole business operation as well as lower sales volume. The main objective of this research study is to identify the actual factors that influencing an effective distribution system of the company. Besides, this study was also purposely done to determine the vendors' perception towards the current distribution system of the company. Furthermore, this study also may provide some recommendations to the company and future researchers. In this study, descriptive research was employed. Sampling frame for this study was taken from the list of vendors that subscribe newspaper from NSTP Kuantan. For this study, probability sampling technique had been used whereby Simple Random Sampling (SRS) was considered to be the most suitable technique for this research study. In order to obtain information during this study, questionnaires, personal interview, and observation have been used as primary data. The conclusion of this study based on the outcome gained from the survey analysis and findings. Through the research, it can be concluded that all four variables, which are transportation, order processing, inventory management, and packaging have the effect on the effectiveness of distribution system. However, the levels of influence vary between each variable. In terms of vendors' perception towards the current distribution system of NSTP Kuantan, the findings show they were neither satisfy nor dissatisfy with the performance. This findings show that, some improvements should be taken into account by the firm in the future.